One‐Pot Enzymatic Synthesis of Cyclic Vicinal Diols from Aliphatic Dialdehydes via Intramolecular C−C Bond Formation and Carbonyl Reduction Using Pyruvate Decarboxylases and Alcohol Dehydrogenases. Issue 21 (13th September 2018) - Zhang, Yan; Yao, Peiyuan; Cui, Yunfeng; Wu, Qiaqing; Zhu, Dunming
Abstract: An enzymatic cascade reaction was developed for one‐pot enantioselective conversion of aliphatic dialdehydes to chiral vicinal diols using pyruvate decarboxylases (PDCs) and alcohol dehydrogenases (ADHs). The PDCs showed promiscuity in catalysing the cyclization of aliphatic dialdehydes through intramolecular stereoselective carbon‐carbon bond formation. Consequently, 1, 2‐cyclopentanediols in three different stereoisomeric forms and 1, 2‐cyclohexanediols in two different stereoisomeric forms could be prepared with high conversion and stereoisomeric ratio from the respective initial substrates, glutaraldehyde and adipaldehyde. These cascade reactions represent a promising approach to the biocatalytic synthesis of important chiral vicinal diols. Abstract :